Inventory management system for Fabretech Resources Sdn Bhd - Muhammad Noramir, Ab Ghani (2019)
Inventory management system is a platform for companies to track their supplies and materials needed to make or build a product to meet the customers` demand. Inventory Management system has been used in companies in many field like food and beverages, manufacturing, agriculture and more. Advanced feature in modern inventory system allow business to perform multiple function including managing the companies` revenues, human resources system and more. In this project, we will focus on designing and developing the suitable inventory system for Fabretech Resources SDN BHD which is a medium sized construction company based in the Klang Valley area